Clinical outcomes of asynchronous telerehabilitation through a mobile app are equivalent to synchronous telerehabilitation in patients with fibromyalgia: a randomized control study - Eren Timurtaş; İrem Hüzmeli; İlkşan Demirbüken; Mine Gülden Polat (BMC Musculoskeletal Disorders)
Abstract Background This study aimed to compare the effectiveness of exercise therapy delivered via a smartphone mobile app, using asynchronous video-based tools, with synchronous telerehabilitation models using videoconferencing for individuals with fibromyalgia syndrome (FMS). Methods The research, utilizing a randomized clinical study design, involves sixty-six FMS patients in an 8-week exercise program. Participants are divided into synchronous (n: 33) and asynchronous (n: 33) groups. Assessments, pain intensity (VAS), functional limitations (FIQr), health-related quality of life (SF 12), catastrophizing (PCS), anxiety and depression (HADS), functional capacity (6MWT), muscle strength (Arm curl test), and joint position sense (LI-RATT), are conducted at baseline, mid-treatment (week 4), end of treatment (week 8). Results No significant group-time interaction was found for total VAS, FIQ, SF 12, PCS, HADS, 6MWT, Arm curl tests, LI-RATT extension, LI-RATT flexion, LI-RATT right rotation scores (p > 0.05). Significant effects of time and interactions between groups and time were observed in the neck (p = 0.010, ES = 0.19) and back region (p = 0.039, ES = 0.19) of the Visual Analog Scale, left rotation score of the LI-RATT (p = 0.008, ES = 0.36), and HADS Anxiety Score (p = 0.029, ES = 0.31). Group differences were significant at all-time points for the outcomes (p < 0.001), except for the right rotation of LI-RATT (p = 0.633). Conclusion The study suggests that asynchronous telerehabilitation is comparable to synchronous methods in addressing pain, quality of life, and other factors in FMS patients. The asynchronous approach may offer advantages in reducing the burden on healthcare professionals and being cost-effective. Future research should explore diverse telerehabilitation protocols and their impact on overall care burdens. Trial registration NCT06299527 (01/03/2024).